2000
DOI: 10.1046/j.1440-1746.2000.02223.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin and bile acids may modulate their own metabolism via regulating uridine diphosphate‐glucuronosyltransferase expression in the rat

Abstract: Our results suggest that bilirubin and bile acids can induce UGT expression and as a result, these compounds may modulate their own metabolism. Such regulation could play a compensatory role in the pathological increased concentrations of these compounds in some hepatobiliary diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 35 publications
0
9
2
Order By: Relevance
“…Our results did not show significantly different pharmacokinetic parameters in patients who had both UGT1A1 * 28 and UGT1A6 * 2 polymorphisms (group B) compared with group A. Li et al [34] suggested that bilirubin can induce the expression of UGTs. Hence, hyperbilirubinemia status in group B may play a compensatory role in modulating UGT expression and partly explain the evidence of no significantly lower PCM-G level in the patients who had both UGT1A1 * 28 and UGT1A6 * 2.…”
Section: Discussioncontrasting
confidence: 72%
“…Our results did not show significantly different pharmacokinetic parameters in patients who had both UGT1A1 * 28 and UGT1A6 * 2 polymorphisms (group B) compared with group A. Li et al [34] suggested that bilirubin can induce the expression of UGTs. Hence, hyperbilirubinemia status in group B may play a compensatory role in modulating UGT expression and partly explain the evidence of no significantly lower PCM-G level in the patients who had both UGT1A1 * 28 and UGT1A6 * 2.…”
Section: Discussioncontrasting
confidence: 72%
“…Only increased Calr and decreased Psmb4 were observed. Although effects from LCA on liver transcription are not well characterized, a previous study showed induction of UGT in primary rat hepatocytes exposed to LCA at a high concentration 100 mM for 48 h (Li et al, 2000). This type of change was not observed in this study.…”
Section: Drugs Not Directly Toxic To Hepatocytes In Vivo or Rarely Tocontrasting
confidence: 75%
“…Consequently, bilirubin induces activity of UGT1A1 (Li et al, 2000); and (2) the gestational hormones, such as progesterone and estrogens, decrease the maternal liver glucuronosyltransferase activity (Luquita et al, 2001). This could also affect the foetus during the gestational period.…”
Section: Discussionmentioning
confidence: 99%